2011
DOI: 10.1021/es1033316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arsenic Compound Amendment on Arsenic Speciation in Rice Grain

Abstract: Rice consumption is a major source of arsenic for Asian populations. Arsenic is present in rice grain both as inorganic arsenic and as dimethylarsinic acid (DMA). It is unclear whether DMA in rice is taken up from the soil or synthesized in planta. We investigated the effect of DMA, methylarsonic acid (MMA) and arsenite amendment on arsenic speciation in rice grain grown in soil and in solution culture. We also investigated the methylation of arsenic in solution culture under suppression of bacterial activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 20 publications
4
31
1
1
Order By: Relevance
“…More importantly, the As methylation and volatilization was influenced by the activity of relative microbes related to As transformation, altered by the input of organic matters into the soil (Huang et al 2012). It was most likely that the methylated As species in rice plants was originated from the rhizosphere under the active of relative methylating microbes in the soil (Arao et al 2011;Lomax et al 2011), so the mehylated As species in the soil solution was absorbed into rice plants, especially in the BGS addition treatments.. The extent of the increase of methylated As was much higher than the inorganic As in the rice grain and husk, due to the fact that methylated As were more liable translocating from roots and shoots to the grains (Carey et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the As methylation and volatilization was influenced by the activity of relative microbes related to As transformation, altered by the input of organic matters into the soil (Huang et al 2012). It was most likely that the methylated As species in rice plants was originated from the rhizosphere under the active of relative methylating microbes in the soil (Arao et al 2011;Lomax et al 2011), so the mehylated As species in the soil solution was absorbed into rice plants, especially in the BGS addition treatments.. The extent of the increase of methylated As was much higher than the inorganic As in the rice grain and husk, due to the fact that methylated As were more liable translocating from roots and shoots to the grains (Carey et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…17−19 However, recent studies have shown that the methylated As species detected in plants are most likely derived from the growth medium originated from microbial methylation. 13,16 The pathway of As methylation and biovolatilization in certain bacteria and fungi, proposed by Challenger and co-workers, 20−22 involves reduction of As(V) to As(III), followed by oxidative methyl transfer from S-adenosyl-L-methionine (SAM) to As(III) catalyzed by arsenite Sadenosylmethionine methytransferase. Arsenic reduction and methylation can continue for several steps forming methylated As species with 1−4 methyl groups.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DMA levels detected in the solution amended by MMA or As(III) with the growth of rice seedlings decreased dramatically after the addition of antibacterial agent chloramphenicol [97]. No methylated As could be detected in plants (rice, tomato and red clover) cultured in a sterile hydroponic solution fed with inorganic As [98].…”
Section: Benefits Of Microbial Arsenic Methylation and Volatilizationmentioning
confidence: 98%
“…It is clear now that methylated As species in rice plant (mostly in the grain) is originated from soil, where microorganisms are responsible for the production of methylated species [97,98]. DMA levels detected in the solution amended by MMA or As(III) with the growth of rice seedlings decreased dramatically after the addition of antibacterial agent chloramphenicol [97].…”
Section: Benefits Of Microbial Arsenic Methylation and Volatilizationmentioning
confidence: 99%